The Impact of Transformational Leadership Dimensions on Teachers' Pedagogical Competence - Badar, Muhammad (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to analyze the influence of transformational leadership dimensions on the pedagogical competence of madrasah teachers. Using quantitative methods, data were collected from 67 teachers using non-probability sampling techniques and analyzed using multiple linear regression. The results showed that idealized influence positively affects teacher pedagogical competence, meaning that the higher the idealized influence, the better the teacher's pedagogical competence. Conversely, inspirational motivation has an adverse effect, indicating that the lower the inspirational motivation, the better the teacher's pedagogical competence. Intellectual stimulation also has a significant effect; the higher the intellectual stimulation, the better the teacher's pedagogical skills. Individualized consideration has a significant effect; the greater the individual attention, the better the teacher's pedagogical competence. Collectively, these four variables affect teacher pedagogical competence. An important finding is the adverse effect of inspirational motivation, which may be due to a lack of support, limited training, or teacher preference for a more relaxed teaching style. This study provides implications for the importance of a balanced leadership strategy in madrasahs, emphasizing the role of idealized influence and intellectual stimulation in improving teaching competence. Schools must provide more professional development opportunities and create a supportive environment to improve teachers' pedagogical skills.